Exploring Software, Tools and Methods used in Web Archive Research - Schmid, Katharina; Healy, Sharon; Byrne, Helena (Digital Preservation Coalition, 2022)
This paper is one part of a larger research project, titled, Web Archives - Researcher Skills and Tools (WARST). In this poster we focus on the data from the WARST study which examines the software, tools and methods used in the web archive research lifecycle.
iPres 2022: International Conference on Digital Preservation
UK
Keywords: web archiving; web archive research; web archive users; web archive creators